Morphological identification and pathology of Myxobolus cyprini and Lamproglena pulchella in some fish in Turkey - Ekinci, Aysel İtik; Saglam, Naim; Özkaraca, Mustafa; Kılınc, Unal (My University, 2022)
This study was performed to investigate the parasites and pathology in the three different fish species, Barbus lacerta, Capoeta trutta and C. umbla, caught in wildlife in Turkey. The fish caught for this study were transported to the laboratory under ethical rules and investigated for parasites. According to the results, two different parasite species (Myxobolus cyprini and Lamproglena pulchella) were morphologically identified. Myxobolus cyprini was found in the soft tissue of the pectoral fins of C. trutta as an off-white, oval cyst. In the histopathological examinations of the cysts, the spores of M. cyprini were observed. Lamproglena pulchella was seen in the gills of B. lacerta. No parasite was also encountered in C. umbla. These parasite species are the first records for wildlife fishes of Uzuncayır Dam Lake of Turkey.
Keywords: Turkey; Fish; parasite; Myxobolus cyprini; Lamproglena pulchella